DIFFERENTIAL ENGLISH SUBSKILL GROWTH AMONG INDONESIAN PRE-SERVICE ELEMENTARY TEACHERS - Disa Evawani Lestari; Risa Fitria (JEE (Journal of English Education), 2026)
This study investigated the differential growth of English proficiency scores among Indonesian pre-service elementary teachers during their first year of study using an explanatory sequential mixed-methods design. The study involved 34 undergraduate students enrolled in an Elementary Teacher Education program utilizing full English-Medium Instruction (EMI) at a university in Indonesia. Quantitative data were collected through pre-test and post-test from TOEFL ITP practice sets. The tests were administered in the beginning of semester one and at the end of semester 2, while qualitative data were obtained through online questionnaires distributed after the post-test, exploring students’ English use habits and learning experiences. The quantitative findings revealed that students’ average English scores increased from 416.12 to 437.56, indicating a progression from CEFR A2 to B1 proficiency levels. However, the growth patterns across subskills were uneven, with Structure and Written Expression demonstrating the greatest growth while Listenign Comprehension showed the least improvement. Interestingly, the qualitative findings revealed an apparent discrepancy as many participants perceived listening as the skill they had improved the most.  Qualitative results indicate that grammatical gains were driven by the students' emerging professional identity, an awareness of their future role as teachers in international schools. The study concludes that while current institutional and digital scaffolds enable students to navigate the linguistic demands of the program, sustainable growth in communicative subskills requires a pedagogical shift from passive input toward interactive classroom discussions and systematic lexical support.